Retrospective analysis of the epidemiology and clinical presentation of West Nile virus infection in horses in South Africa, 2016 - 2017 - Thompson, P.N. (Peter N.) (University of Pretoria, 2024)
Dissertation (MSc (Veterinary Epidemiology))--University of Pretoria, 2019.